Acute anti‐obesity effects of intracerebroventricular 11β‐HSD1 inhibitor administration in diet‐induced obese mice. (25th March 2018) - Seo, M.; Islam, S. A.; Moon, S.‐S.
Abstract : The hypothalamus is the regulatory centre of both appetite and energy balance and endoplasmic reticulum (ER) stress in the hypothalamus is involved in the pathogenesis of obesity. Recently, inhibition of 11 β hydroxysteroid dehydrogenase type1 (11β‐HSD1) was reported to have an anti‐obesity effect by reducing fat mass. However, the link between the role of 11β‐HSD1 in the hypothalamus and obesity has yet to be determined. In the present study, embryonal primary hypothalamic neurones and high‐fat diet (HFD) fed mice were used to investigate the anorexigenic effects of 11β‐HSD1 inhibitors both in vitro and in vivo. In hypothalamic neurones, carbenoxolone (a non selecitve 11β‐HSD inhibitor) alleviated ER stress and ER stress‐induced neuropeptide alterations. In HFD mice, i.c.v. administration of carbenoxolone or KR67500 (nonselective and selective 11β‐HSD1 inhibitors, respectively) was associated with less weight gain compared to control mice for 24 hours after treatment, presumably by reducing food intake. Furthermore, glucose regulated protein ( Grp78 ), spliced X‐box binding protein ( Xbp‐1s ), c/EBP homologous protein ( chop ) and ER DnaJ homologue protein ( Erdj4 ) expression was decreased in the hypothalami of mice administrated 11β‐HSD1 inhibitors compared to controls. Conversely, the phosphorylation of protein kinase B (PKB/Akt), signal transducer and activator of transcription 3 (Stat3), mitogen‐activated protein kinase (MAPK/ERK) and S6 kinase1 (S6K1) in the hypothalamus was induced more in mice treated using the same regimes. In conclusion, acute 11β‐HSD1 inhibition in the hypothalamus could reduce food intake by decreasing ER stress and increasing insulin, leptin, and mammalian target of rapamycin complex 1 (mTORC1) signalling.